New York Paper - Supplementary Note on Blast-Furnace Lines - Edward Walsh (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1889)
The difficulty of securing for experimental research the actual conditions to be found in practice very frequently deters many from engaging in such work. Probably no metallurgical operation is more difficult to imitate in the laboratory than the blast-furnace process. So many complex reactions take place within the furnace, under such varied conditions of time and temperature, with innumerable mechanical, physical, and chemical mutations, that while the results reached may approximate those obtained in practice, there is always something wanting. Much work of this kind has, nevertheless, been done, and is now being undertaken. We are indebted to the bold minds who have attempted it for our present real knowledge of the blast-furnace process. Not that those who have performed series of experiments at a few given temperatures can claim the honor. It required more than this—the ability to make a summary of all preceding experiments, to supply those which were wanting, and to confirm those that were doubtful. Sir I. Lowthian Bell, whose able papers before the Chemical Society and the British Iron and Steel Institute (forming the basis of his great work, The Chemical Phenomena of Iron-Smelting) has